Proteomic analysis response of rice (Oryza sativa) leaves to ultraviolet-B radiation stress - Sah, Saroj Kumar; Jumaa, Salah; Li, Jiaxu; Reddy, K. Raja (Frontiers in Plant Science, 2022)
Rice (Oryza staiva) is a staple food for human and serves as a model organism for genetic and molecular studies. Few studies have been conducted to determine the effects of ultraviolet-B (UV-B) stress on rice. UV-B stress triggers morphological and physiological changes in plants. However, underlying mechanisms governing these integrated responses are unknown. In this study, we conducted proteomic response of rice leaves to UV-B stress using two-dimensional gel electrophoresis and identified the selected proteins by mass spectrometry analysis. To determine changes in protein accumulation in response to UV-B stress four levels of daily biologically effective UV-B radiation intensities were imposed: 0 (control), 5, 10, and 15 kJ m-2 d-1in two cultivars, i.e., IR6 and REX. To mimic the natural environment, we conducted this experiment in Sunlit Soil-Plant-Atmosphere-Research (SPAR) chambers. Among the identified proteins, 11% differentially expressed proteins were found in both cultivars. In Rex, only 45% of proteins are differentially expressed while only 27.5% were expressed in IR6. The results indicate that REX is more affected by UV-B stress than IR6 cultivars. The identified protein TSJT1 (spot no.16) in both the cultivars plays a crucial a role in plant growth and development during stress treatment. Additionally, we found that UV-B stress altered many antioxidants enzymes associated with redox homeostasis and cell defense response. Another enzyme, the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has been identified as spot no.15, which played an essential role in glycolysis and cellular energy production. Another important protein identified is glycosyl hydrolase (GH) as spot no.9, which catalyzes the hydrolysis of glycosidic bonds in cell wall polymers and significantly affects cell wall architecture. Some identified proteins are related to photosynthesis, protein biosynthesis, signal transduction, and stress response. The findings of our study provide new insights to understand how rice plants tailored to UV-B stress via modulating the expression of UV-B responsive proteins, which help develop superior rice breeds in the future to combat the UV-B stress. Data are available via ProteomeXchange with identifier PXD032163